Community perceptions and attitudes toward serious mental illness in Cambodia - Bunna Phoeun; Sareth Khann; Chanthorn Leang; Thea Soung; Kevin Conroy; Amanda J. Nguyen (Elsevier, 2024)
Background: Worldwide, approximately 64 million people are living with serious mental illnesses (SMI), such as schizophrenia and bipolar disorder. Because community perceptions and attitudes can impact help-seeking and the course of illness, understanding and incorporating these perspectives, and addressing misconceptions and harmful attitudes, is a critical component of comprehensive mental health support. These concepts are deeply rooted in local culture and belief systems, yet research to provide local understanding is often lacking, particularly in low- and middle-income countries. Objective: The aim of this study was to assess relative caregivers' and other key community members' perceptions and attitudes towards people with SMI in Cambodia. Methods: A brief survey that included open-ended assessment of mental health knowledge and beliefs was interviewer-administered to 115 relative caregivers of people with SMI. Additionally, 20 community members considered knowledgeable about mental health (e.g., traditional healers, local authorities, family caregivers) participated in semi-structured qualitative interviews that explored perceptions and attitudes toward SMI in Cambodia. Results: Participants included 56 men and 79 women. While respondents were able to identify signs and symptoms of SMI, the most commonly perceived causes were spiritual (e.g., spells, ghosts); family crisis (e.g., domestic violence); and physical health problems. Both respondent groups showed empathy for people with SMI (e.g., pity) but also reported feelings of fear and shame (e.g., perceived tendency toward violence and not wanting to live with such a person). Conclusion: Both caregivers likely to seek help and respected local figures likely to be involved in initial help-seeking efforts demonstrated limited understanding of SMI as a medical disorder suitable for management within the formal healthcare system. Commonly reported misperceptions are likely to lead to delayed access to care and poorer treatment within the community. Strengthening mental health knowledge among caregivers and key community leaders may hold promise for improving peer support and community referral pathways.